Assembling Class Actions - Samuel Issacharoff (Washington University Law Review, 2013)
Five times in the past few years, the Supreme Court has engaged the propriety of class actions. Taken together, these cases revisit certain core issues in class action law, all turning on the need and justification for grouping individuals as part of a collective entity for litigation purposes. When examined from the perspective of legal treatment of individuals as part of a collective—assembling the class action, in the terminology of the title—three distinct aspects of class organization stand out. First, the existence of a litigation entity requires that someone be in charge, and that in turn raises the problem of how to ensure the faithfulness of the appointed agent. Second, the decision to forge a litigation entity necessarily empowers one side of the dispute relative to the other side, and that requires some justification. And, finally, even when litigation entities exist, class action law must come to terms with the range of individual autonomy that should still be recognized, including the ability to contract out of collective representation. As developed in the difficult recent class action cases, the questions of leadership, underwriting, and autonomy help define how modern class action practice endeavors to provide equality of treatment and predictability in the interaction between the individual insults of aggrieved citizens and the undiscriminating consequences of mass society.
Keywords: class action; collective; representation; autonomy